El requinto de Byron Macías. Transcripción de piezas instrumentales inéditas de música ecuatoriana - Castillo Minga, Oscar Andrés (2025)
The present document of foundation for the artistic proposal, seeks to provide a theoretical support to the project entitled El Requinto of Byron Macías: Transcription of unpublished instrumental pieces of Ecuadorian Music. As the main objective of this project is to transcribe ten original unpublished instrumental pieces for the requinto belonging to Ecuadorian music within the genres pasillo, albazo, sanjuanito, and bomba. The methodological process consisted of three phases. In the first phase, it was realized the selection of the works that form part of the artistic proposal, these are: Río cristal, Mi Génesis, Sarita, Brisas del alma, Carmen María, Elizabeth, Añoranzas, Mestizo, Caricias de Mamá, and El camino. Later, in the second phase, it was carried out the transcription of the selected works using the music notation software Finale 26 Make Music, employing descriptive details in order to reflect the greatest possible range of elements and techniques that present the works performed by the composer. Finally, the third phase it was developed the diffusion of the artistic proposal through a live recital featuring a selection of repertoire, in addition, the publication of a booklet containing the transcribed works. As a result of this work, it has presented the ten transcriptions, in some cases are for soloist requinto and others for two requintoes. Once the artistic proposal was completed, this project can be considered as a valuable contribution to the rescue and preservation of Ecuadorian music, as well as a significant resource for teachers, students, requinto players, and for future researches in general